Sistem Informasi Rental PlayStation Berbasis Client-Server: Evaluasi Penerimaan Pengguna Menggunakan Technology Acceptance Model - Setyadi, Dian Febry; Wibowo, Adityo Permana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Effective operational management is a critical aspect in the PlayStation rental business as it plays a role in ensuring service smoothness and supporting comprehensive business oversight. At Bossman PlayStation, operational processes are still managed manually using conventional recording methods. This condition results in slow customer service (average 4 minutes per transaction), vulnerability to transaction and inventory recording errors (3-5 errors per week) that potentially cause financial losses, and limited owner capability to monitor business development in real-time. This study aims to design an integrated information system with a client-server architecture whose solution includes two main platforms: Mobile Application to accelerate daily employee operations, and Web Application focused on monitoring and approval functions by the owner. The system design uses a UML-based approach to model requirements and workflows, utilizing WebSocket technology to provide real-time unit status updates and database triggers to automate business rules such as stock updates. The achieved result is a mature and detailed system design, where all main workflows including two rental models, sales transactions, to approval processes have been clearly defined and are ready for implementation. Functional testing showed 100% success in 10 main scenarios, and user acceptance testing (TAM) obtained a score of 4.525/5.0. The system successfully reduced transaction time to 1 minute and eliminated recording errors.